Essays on aid, growth and welfare - Gomanee, Karuna (2002)
As from early 1960s, the question of whether aid works has been a central theme in development economics. The continued effort to analyse the effects of aid only now appears to be nearing consensus. A close examination of the literature suggests that there are certain aspects that are critical to this strand of studies that have not been fully addressed. In this thesis, we make a contribution by throwing light on three such issues that relate to the macroeconomic effectiveness of aid.